2016
DOI: 10.1016/j.jaci.2015.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of lung ventilation defects in asthmatic children

Abstract: The lung defect volume percentage measured by using (3)He MRI correlates with several clinical features of asthma, including severity, symptom score, medication requirement, airway physiology, and atopic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
4
42
0
Order By: Relevance
“…Data from studies in adults suggest that the size and location of ventilation defects tends to persist over weeks to years34 and are more commonly found in the lung periphery and correspond to areas of air trapping on multidetector CT 35. In the only paediatric study that included preschool children, there was no effect of age on the detection of ventilation defects suggesting that these peripheral defects may be present from an early age 33. Abnormalities are commonly seen in conventional chest X-rays of infants and preschool children with RW, and recent evidence would suggest that radiological abnormalities predict more severe disease 8.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Data from studies in adults suggest that the size and location of ventilation defects tends to persist over weeks to years34 and are more commonly found in the lung periphery and correspond to areas of air trapping on multidetector CT 35. In the only paediatric study that included preschool children, there was no effect of age on the detection of ventilation defects suggesting that these peripheral defects may be present from an early age 33. Abnormalities are commonly seen in conventional chest X-rays of infants and preschool children with RW, and recent evidence would suggest that radiological abnormalities predict more severe disease 8.…”
Section: Discussionmentioning
confidence: 98%
“…This study showed that LCI is significantly increased in infants with prenatal tobacco smoke exposure and infants who had a lower respiratory tract infection in the first year of life,32 suggesting these changes may correlate with early structural lung impairment; however, no imaging data were available to correlate these functional tests with imaging. Ventilation heterogeneity imaging is limited in RW and asthma, but persistent ventilation defects have been noted in asthmatics children compared with HC 33. Data from studies in adults suggest that the size and location of ventilation defects tends to persist over weeks to years34 and are more commonly found in the lung periphery and correspond to areas of air trapping on multidetector CT 35.…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of normal healthy controls in our study might explain this discrepancy. Since height and weight have also been shown to influence the regression equations in many FOT indexes, we generated Asymmetric branching of the bronchial tree may cause discrepancies in the anatomic and acoustic characteristics of the central and peripheral airways, and lung ventilation defects are not uniformly distributed in asthmatic lungs [26]; hence, it has been argued that R5-R20 merely represents the frequency-dependence of resistance or the heterogeneity of airway resistance rather than the true resistance of peripheral airways [27]. Historically, however, it has been presumed that R5, R20, and R5-R20 represent the resistances of the whole, central-large, and peripheral-small airways, respectively.…”
Section: Salivary Sp-d Levels Correlate With R5-r20 In Asthmatic Chilmentioning
confidence: 99%
“…Recently, lung defect volume percentage was found to correlate with several clinical features of asthma such as severity, symptom score, medication requirement, airway physiology, and atopic markers in children with mild and severe asthma (40). Another recent study (41) using helium-3 MR in a subset of 44 children participating in the Childhood Origins of Asthma (COAST) study (42)found that children with asthma had more and larger ventilation defects and a greater degree of restricted gas diffusion (lower average root-mean-square diffusion length) than non-asthmatic children in this cohort, without correlation between the two measures.…”
Section: Use Of Hp Gas Mri In Childrenmentioning
confidence: 99%